2011
DOI: 10.1246/cl.2011.1127
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Continuous Production of Hexagonal Boron Nitride Powders

Abstract: An intermediate-frequency furnace was used for continuous production of hexagonal boron nitride (h-BN) by heating a mixture of C3N6H6 and H3BO3 in a flowing nitrogen gas at 1800–1950 °C. The products were examined by XRD, Raman, FTIR, and SEM. The results indicate the as-synthesized products are h-BN flakes with a purity of 98.73 wt %. A possible reaction mechanism is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…This synthetic procedure typically utilizes boric acid and melamine as reactants, relying solely on the reduction of boron by oxidation of an organic material as a source of nitrogen. During these reactions, flue gases such as NO x and CO x are generated in an inert atmosphere. , These reactions have been reported and described earlier by several researchers. , Other research has demonstrated the formation of melamine diborate (M2B), which occurs as a result of hydrogen bonding between melamine and boric acid . Under thermal treatment, the produced crystalline material forms the precursor of h-BN, (B 4 N 3 O 2 H), which is then converted to h-BN under high temperatures under inert atmospheres.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…This synthetic procedure typically utilizes boric acid and melamine as reactants, relying solely on the reduction of boron by oxidation of an organic material as a source of nitrogen. During these reactions, flue gases such as NO x and CO x are generated in an inert atmosphere. , These reactions have been reported and described earlier by several researchers. , Other research has demonstrated the formation of melamine diborate (M2B), which occurs as a result of hydrogen bonding between melamine and boric acid . Under thermal treatment, the produced crystalline material forms the precursor of h-BN, (B 4 N 3 O 2 H), which is then converted to h-BN under high temperatures under inert atmospheres.…”
Section: Introductionmentioning
confidence: 84%
“…In one of the most feasible methods of synthesis, boric acid and melamine are exposed to high temperatures in an inert atmosphere . This method is one of the safest because, unlike other techniques where ammonia and hydrogen gases are used, this one employs only nonhazardous gases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 The preparation method via reduction of melamine diborate (M2B) is considered the safest one as high pressure and flammable or toxic gases such as hydrogen or ammonia are not needed. 43 h-BN can take different nanoscale morphologies depending on the applied synthesis method and the conditions used during preparation. 44 Different h-BN nanostructures have been reported by other researchers, such as nanotubes, 45 nanosheets, 46 nanomeshes, 48 nanoscrolls, 47 nanoflower-shaped materials, 48 and nanoribbons which have similar characteristics to graphene.…”
Section: Introductionmentioning
confidence: 99%
“…All of those methods are similar in that they use high temperatures (up to 1873 K) and high pressures (up to 5 GPa) . The preparation method via reduction of melamine diborate (M2B) is considered the safest one as high pressure and flammable or toxic gases such as hydrogen or ammonia are not needed . h-BN can take different nanoscale morphologies depending on the applied synthesis method and the conditions used during preparation .…”
Section: Introductionmentioning
confidence: 99%